SUKSES BERINTERAKSI DENGAN ANAK TIRI (Studi Kasus Nabi Shallallahu ‘alaihi wa sallam Bersama Anak Tiri Beliau) - Muhamad Arifin (Al-Majaalis : Jurnal Dirasat Islamiyah, 2021)
The existence of stepchild in a household is often the source of the household disharmony between husband and wife. It is common for this disharmony to lead to divorce.On the other hand, the stepchild often receives discriminatory and even cruel treatment. By using the descriptive analysis method, the author collected the data on the life of the Prophet -peace and blessings of Allah be upon him- with his stepchildren.Then the data were analysed, in order to reveal his practical and applicabletips from living with the stepchildren. The author madethe Prophet life with his stepchildren the object of research, asthe Prophet is a role model for mankind in every aspect of life. He had of course taught a set of applicable and effective tips in living a married life with his stepchildren. Moreover, he married ten widowed women who all had children from their previous marriage. From analysing these data, the author found at least six practical tips that the Prophet exemplified so that he succeeded in interacting with all of his stepchildren.From this research, the author concluded that one of the solutions to the success of the Prophet -peace and blessings of Allah be upon him-in interacting with his stepchildren is because he positioned them as one of the keys to the Prophet’s marriage with their mothers and as one of the keys to happiness in the household. Likewise, the Prophet never perceived his stepchildren as a threat to the peace of his household.